2012
DOI: 10.1590/s1516-35982012000300029
|View full text |Cite
|
Sign up to set email alerts
|

Santa Inês sheep supplementation on urochloa grass pasture during the dry season: intake, nutrient digestibility and performance

Abstract: -This study was conducted with the objective of evaluating the effect of concentrate supplementation, formulated with different ingredients (Mesquite pod meal, sorghum meal or wheat meal and mineral supplementation) on performance, intake and digestibility of nutrients in Santa Inês lambs grazing on urochloa grass during the dry season. Twentyfour uncastrated weaned Santa Inês sheep, with average body weight (BW) 20±2 kg with an average of 120 days of age were used in the assay. The experiment lasted 75 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The DM, CP and NDF apparent digestibility was affected by supplementation, more due to the higher digestibility of the concentrate than to the forage itself (Almeida et al, 2012), shown by the lower digestibility of NDF for the control group in this study. In the present study, better digestibility of DM in supplemented groups was obtained in WB.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The DM, CP and NDF apparent digestibility was affected by supplementation, more due to the higher digestibility of the concentrate than to the forage itself (Almeida et al, 2012), shown by the lower digestibility of NDF for the control group in this study. In the present study, better digestibility of DM in supplemented groups was obtained in WB.…”
Section: Discussionmentioning
confidence: 54%
“…Studies have evaluated different sources of supplement for grazing lambs in the dry season (Almeida et al, 2011(Almeida et al, , 2012) but a few studies have been made during the rainy season (Godfrey and Dodson, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The use of mesquite pod meal (Prosopis juliflora (Sw.) D.C.) as a substitute for corn becomes an alternative due to its easy accessibility in semiarid regions and its use in diets for small ruminants has shown better productive indices compared to corn (8)(9)(10)(11)(12)(13) . However, the consumption of P. juliflora pods as the main source of food causes intoxication in animals (14)(15)(16) .…”
Section: Introductionmentioning
confidence: 99%